Effects of pre-adult photoperiod experience on reproductive parameters of Chrysoperla nipponensis (Tjeder): potential implications for mass-rearing of natural enemies - Kong, Xue; Xu, Minghui; Li, Haolin; Zhong, Shaofeng; Li, Dandan; Xu, Yongyu; Chen, Zhenzhen (Frontiers in Insect Science, 2025)
Photoperiod is a critical environmental factor for insect development and physiology, yet little is known about the effects of photoperiodic signals received during photoperiod-sensitive stages on reproductive parameters. The green lacewing, Chrysoperla nipponensis, is a promising candidate for mass rearing in biological control. Photoperiod is the primary environmental factor influencing C. nipponensis reproductive diapause. This study investigates how photoperiodic cues during photoperiod-sensitive stages affect key reproductive parameters such as fecundity, lifespan, oviposition duration, oviposition rate, diapause rate, pre-oviposition period, and lipid content of C. nipponensis. The results showed that short-day conditions (Light:Dark = 9h:15h; L9:D15) during pre-adult stages increase total lipid and triglyceride levels in both third larvae and newly emerged females, thereby enhancing fecundity of female, without reducing lifespan or oviposition. Furthermore, long-day conditions (Light:Dark = 15h:9h; L15:D9) during the pre-adult stage inhibited diapause, while increasing fecundity and extending oviposition duration. Our findings demonstrate that photoperiodic signals during the pre-adult stages significantly affect the reproductive parameters of C. nipponensis, which advances the understanding of photoperiod-dependent reproductive diapause and offers novel insights for optimizing strategies in mass-rearing of natural enemies.